Static culture of scenedesmus dimorphus in filtered sago effluent - Nur Wahida, Bt Bandah (Universiti Malaysia Sarawak (UNIMAS), 2010)
Scenedesmus dimorphus which is a photosynthetic algae, can serve as a source of biofuel due to the high lipid content, 16-40% . The growth of Scenedesmus dimorphus in FSE is observed with optical density (560nm) every 2 days and biomass is determined according to dry cell weight (DCW). In the effects of Sodium bicarbonate concentration, biomass produced in 0 g/L NaHCO3 was highest with 348 mg/L and 568 mg/L respectively on 14 day cultivation. Biomass produced from 8 g/L of NaHCO3 was 100 mg/L and 248 mg/L. Maximum biomass from this medium was at 396 mg/L. Biomass produced from 16 g/L of NaHCO3 was 120 mg/L and 216 mg/L with maximum biomass achieved was at 420 mg/L on 14 day of cultivation. Biomass produced from CHU medium was 361 mg/L and maximum biomass achieved in this medium was at 361 mg/L on 16 days of cultivation. Scenedesmus dimorphus was successfully cultivated in filtered sago effluent and the best parameter for the growth and a highest lipid percentage achieved was addition of 16 g/L NaHCO3 with maximum biomass achieved was at 420 mg/L on day 14 of cultivation and 16% of lipid percentage. Hence, FSE can be used beneficially without disposing into rivers thus minimizing environmental pollution.